2002
DOI: 10.4049/jimmunol.169.7.3934
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Receptor-Associated Kinase and Low Molecular Weight GTPase RhoA Signal Molecules Are Required for Bacterial Lipopolysaccharide-Induced Cytokine Gene Transcription

Abstract: Proinflammatory cytokines such as IL-1, TNF, IL-6, and IL-8 are produced by leukocytes in response to bacteria or bacterial components. A great deal has been learned during the past few years about the synthesis and release of proinflammatory cytokines by leukocytes; however, relatively little is known about the intracellular events that lead to leukocyte proinflammatory cytokine gene transcription. This study examined the signal transduction pathway of IL-8 induction by bacterial LPS. Stimulation of monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 39 publications
0
44
1
Order By: Relevance
“…Furthermore, studies have shown that inhibitors of Rho GTPases block the stimulation of macrophages with a mycoplasmal lipoprotein (25). A role for RhoA in TLR4-induced cytokine expression was postulated by two groups using different experimental approaches and cell types (26,27). We show in this study that RhoA controls a signaling cascade, which regulates NF-B trans activation without affecting I-B degradation.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, studies have shown that inhibitors of Rho GTPases block the stimulation of macrophages with a mycoplasmal lipoprotein (25). A role for RhoA in TLR4-induced cytokine expression was postulated by two groups using different experimental approaches and cell types (26,27). We show in this study that RhoA controls a signaling cascade, which regulates NF-B trans activation without affecting I-B degradation.…”
Section: Discussionmentioning
confidence: 79%
“…From a pathophysiological point of view it is important that C3 was shown to alter for example epithelial and endothelial barrier functions (Nusrat et al 1995;Stamatovic et al 2003), the signaling of immune cells including phagocytosis (Caron and Hall 1998), the production of cytokines (Chen et al 2002;Dreikhausen et al 2001), adhesion (Laudanna et al 1996), de-adhesion , and migration of immune cells (Worthylake et al 2001;Millan and Ridley 2005). A very recent study reported that C3stau-producing S. aureus form transcellular tunnels by inactivation of Rho, so-called macroapertures, which lead to the loss of barrier function in endothelial cells (Boyer et al 2006).…”
Section: The Pathogenetic Role Of C3-like Exoenzymesmentioning
confidence: 99%
“…Numerous stimuli can activate NF-B, including LPS, as well as other proinflammatory factors, such as TNF-␣ and IL-1 (8,9). Indeed, the LPSinduced activation of NF-B appears essential for proinflammatory cytokine synthesis in human peripheral blood monocytes (10).…”
mentioning
confidence: 99%